2011
DOI: 10.1111/j.1471-4159.2010.07033.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases A2 and neural membrane dynamics: implications for Alzheimer’s disease

Abstract: J. Neurochem. (2011) 116, 813–819. Abstract Phospholipases A2 (PLA2s) are essential enzymes in cells. They are not only responsible for maintaining the structural organization of cell membranes, but also play a pivotal role in the regulation of cell functions. Activation of PLA2s results in the release of fatty acids and lysophospholipids, products that are lipid mediators and compounds capable of altering membrane microdomains and physical properties. Although not fully understood, recent studies have linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 87 publications
1
54
0
Order By: Relevance
“…PLA 2 s also have a role in modification of the physical properties (such as fluidity) of cellular membranes; because amyloid precursor protein (APP) is a transmembrane protein, membrane fluidity may be of great importance to platelet formation in AD (Lee et al, 2011). Moreover, several previous works (Colangelo et al, 2002; Gattaz et al, 1995, 1996; Ross et al, 1998; Talbot et al, 2000) have shown that PLA 2 activity and expression in the AD brain and central nervous system seem to be correlated with the progression of AD.…”
Section: Discussionmentioning
confidence: 99%
“…PLA 2 s also have a role in modification of the physical properties (such as fluidity) of cellular membranes; because amyloid precursor protein (APP) is a transmembrane protein, membrane fluidity may be of great importance to platelet formation in AD (Lee et al, 2011). Moreover, several previous works (Colangelo et al, 2002; Gattaz et al, 1995, 1996; Ross et al, 1998; Talbot et al, 2000) have shown that PLA 2 activity and expression in the AD brain and central nervous system seem to be correlated with the progression of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the key enzyme involved in the turnover and degradation of LPE, phospholipase A 2 (PLA 2 ), is markedly increased in brains from AD patients (Farooqui, 2010) and associated to AA production in AD (Sanchez-Mejia and Mucke, 2010). Also, PLA 2 activation has been linked to inflammation process in a genetically model of neurodegeneration, since it showed that specific lysophospholipids were responsible for microglial activation and the cytosolic PLA2 (cPLA2) inhibition had neuroprotective effect (Lee et al, 2011; Sundaram et al, 2012). According to our results, BACE1 silencing down-regulated the composition of AA in LPE at 6 and 12 months post-treatment, and decreased the phosphorylation state of cPLA 2, which could be involved in the cell membrane homeostasis of treated AD mice at 12 months post-injection, with the consequent down-regulation of AA levels and COX2 pro-inflammatory pathway in the same time-line ( Figures 7C,D ), suggesting a more effective anti-inflammatory regulation by the long-term BACE1’s silencing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of PLA 2 results in the release of fatty acids and lysophospholipids, which are capable of altering membrane microdomains and physical properties. Recent studies have linked aberrant PLA 2 activity to oxidative signaling pathways involving NADPH oxidase that underlie the pathophysiology of neurodegenerative diseases [176]. NADPH oxidase generates superoxide by transferring electrons from NADPH inside the cell and coupling these to molecular oxygen to produce superoxide anion (a free radical).…”
Section: Possible Links Between Ad Associated Lipid Changes and Slow mentioning
confidence: 99%